2022
DOI: 10.3389/fpsyg.2022.806460
|View full text |Cite
|
Sign up to set email alerts
|

Physical Appearance Perfectionism: Psychometric Properties and Factor Structure of an Assessment Instrument in a Representative Sample of Males

Abstract: Perfectionism is a multidimensional construct with both positive and negative aspects. Recently, the concept of appearance-oriented perfectionism has been introduced, which is associated with body image dissatisfaction and weight and shape control behaviors. The Physical Appearance Perfectionism Scale (PAPS) is a 12-item two-factor instrument developed to assess this new dimension of perfectionism. The aim of the study is to validate the Spanish version of PAPS among a representative sample of 850 male univers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 40 publications
0
1
0
Order By: Relevance
“…A specific variable that plays an important role in social physique anxiety is physical appearance perfectionism [ 8 , 9 ]. Previous studies have shown that individuals with high physical appearance perfectionism believe that their appearance is flawed and compare their appearance with others.…”
Section: Introductionmentioning
confidence: 99%
“…A specific variable that plays an important role in social physique anxiety is physical appearance perfectionism [ 8 , 9 ]. Previous studies have shown that individuals with high physical appearance perfectionism believe that their appearance is flawed and compare their appearance with others.…”
Section: Introductionmentioning
confidence: 99%